2015
DOI: 10.1016/j.jbiomech.2014.11.032
|View full text |Cite
|
Sign up to set email alerts
|

Effects of asymmetrical stance and movement on body rotation in pushing

Abstract: Pushing objects in the presence of body asymmetries could increase the risk of back injury. Furthermore, when the object is heavy, it could exacerbate the effects induced by asymmetrical posture. We investigated how the use of asymmetrical posture and/or upper extremity movement affect vertical torque (Tz) and center of pressure (COP) displacement during pushing. Ten healthy volunteers were instructed to push objects of three different weights using two hands (symmetrical hand use) or one hand (asymmetrical ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…Second, the increased COP displacement during the balance restoration phase after the pushing movement, combined with slow reaction time seen in older adults (Stelmach, Populin, 1990), might predispose them to even larger instability making it more difficult to regain balance. It was also demonstrated that when young subjects push heavier objects, they show increased magnitudes of COP displacement and vertical torque (Lee and Aruin, 2015). As such, one could suggest that when older adults are required to push heavier objects, their inability to control the COP magnitude and displacement might predispose them to losing their balance and potentially falling.…”
Section: Discussionmentioning
confidence: 99%
“…Second, the increased COP displacement during the balance restoration phase after the pushing movement, combined with slow reaction time seen in older adults (Stelmach, Populin, 1990), might predispose them to even larger instability making it more difficult to regain balance. It was also demonstrated that when young subjects push heavier objects, they show increased magnitudes of COP displacement and vertical torque (Lee and Aruin, 2015). As such, one could suggest that when older adults are required to push heavier objects, their inability to control the COP magnitude and displacement might predispose them to losing their balance and potentially falling.…”
Section: Discussionmentioning
confidence: 99%
“…Approximately 25% of nurses declare that they always lift weights ergonomically, bending lower limbs and keeping the spine straight . Adoption of forced, asymmetrical body postures and a long‐standing position during work can affect the improper use of the feet through the asymmetry of the distribution of the load on the feet …”
Section: Introductionmentioning
confidence: 99%
“…5 Adoption of forced, asymmetrical body postures and a long-standing position during work can affect the improper use of the feet through the asymmetry of the distribution of the load on the feet. 16,17 Functional efficiency of the foot is determined by its musculoskeletal efficiency, bone structure and the loads it undergoes during everyday activity. The method of loading and setting of the foot is often the result of biomechanical relationships concerning other parts of the movement system.…”
mentioning
confidence: 99%
“…To address the aforementioned concerns, we have been developing a method for measuring foot position using a single inertial sensor on trunk and shoe-type force sensors [ 19 ]. Previous studies have shown that the use of an inertial sensor on the trunk and shoe-type force sensors can be considered an effective method for measuring foot position given the relationship between trunk movement and foot position during manual handling [ 9 , 20 , 21 , 22 , 23 ]. Wagner et al found that a wide-footed stance is related to trunk rotation during manual lifting tasks [ 20 ].…”
Section: Introductionmentioning
confidence: 99%